2022
DOI: 10.1007/s10869-022-09794-3
|View full text |Cite
|
Sign up to set email alerts
|

Granting Leadership to Asian Americans: the Activation of Ideal Leader and Ideal Follower Traits on Observers’ Leadership Perceptions

Abstract: Despite demonstrating high levels of academic and professional competence, Asians are underrepresented in leadership roles in North America. The limited research on this topic has found that Asian Americans are perceived by others as poorer leaders than White Americans due to perceptions that Asians lack the ideal traits of a Western leader (i.e., agentic) relative to White Americans. However, we contend that, in addition to poorly activating ideal leader traits, Asian Americans may strongly activate ideal fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Specifically, there was greater use of agentic terms in letters for applicants who self-identify as Asian or "other/not reported." Although this finding is at odds with the documented perception that Asians lack agentic traits, 18 it is in keeping with findings that letter writers in other specialties use more agentic language with Asian applicants and non-white applicants. 19 Further, SLOEs had significantly more communal language and less agentic language, regardless of gender (Table 4).…”
Section: Discussionsupporting
confidence: 70%
“…Specifically, there was greater use of agentic terms in letters for applicants who self-identify as Asian or "other/not reported." Although this finding is at odds with the documented perception that Asians lack agentic traits, 18 it is in keeping with findings that letter writers in other specialties use more agentic language with Asian applicants and non-white applicants. 19 Further, SLOEs had significantly more communal language and less agentic language, regardless of gender (Table 4).…”
Section: Discussionsupporting
confidence: 70%
“…For example, Rosette et al (2016) theorized that Asian and Black women leaders face unique challenges due to how the prevailing stereotypes associated with these racialized identities relate to perceptions of agentic deficiency (Black women being stereotyped as not possessing agentic competence) and agentic penalty (Asian women being stereotyped as not possessing agentic dominance). Moreover, research on ideal follower and leader traits showed how stereotypes might be more likely to emerge when raters are in competition with those they are evaluating (Kim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research on ideal follower and leader traits showed how stereotypes might be more likely to emerge when raters are in competition with those they are evaluating (Kim et al, 2022).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Conversely, compared to male leaders, female leaders were perceived as having more status (Study 1) or equal status (Study 2). One possible explanation is that without a direct threat, such as limited leadership positions, there might be no bias against groups based on static status characteristics such as gender or race (e.g., Kim et al, 2022 ). Another potential explanation for our findings might stem from participants’ awareness of prevalent research and expectations regarding gender stereotypes and bias.…”
Section: Discussionmentioning
confidence: 99%